PRAKTIK AKUNTANSI MANAJEMEN UNTUK MENINGKATKAN PRODUKTIVITAS USAHA TANI JAGUNG DI DESA BULOILA KECAMATAN SUMALATA KABUPATEN GORONTALO UTARA - Kamasi, Sri Putriyanti (JSAP : Journal Syariah and Accounting Public, 2023)
Implementation of accounting for small and medium entities, helping business actors implement management in business. Recording from business transactions to producing balance sheets and profit and loss reports helps business actors to maintain the continuity of their business. This research aims to find out how management accounting practices can be applied effectively in corn farming businesses to increase productivity in Buloila Village, Sumalata District, North Gorontalo Regency. This research uses qualitative methods using data collection techniques through interviews and documentation. The informant did not know the correct recording of reproduction costs so he did not record them in determining production costs and felt that recording was not that important so after analysis it was found that there was a difference in total production costs which lay in factory overhead costs